1971
DOI: 10.1002/pol.1971.150090307
|View full text |Cite
|
Sign up to set email alerts
|

Free‐radical homopolymerization and copolymerization of vinylferrocene

Abstract: The benzene solution homopolymerization of vinylferrocene, initiated by azobisisobutyronitrile, gave a series of benzene‐soluble homopolymers. Thus, free‐radical copolymerization studies were performed with styrene, methyl acrylate, methyl methacrylate, acrylonitrile, vinyl acetate, and isoprene in benzene. With the exception of vinyl acetate and isoprene, which did not give copolymers with vinylferrocene under these conditions, smooth production of copolymers occurred. The relative reactivity ratios, r1 and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
2

Year Published

1975
1975
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(25 citation statements)
references
References 23 publications
1
22
0
2
Order By: Relevance
“…This results in low molecular weights in a conventional radical polymerization initiated with AIBN (M -n above 12 000 g/mol is rarely described in literature). Also the double bond of vinylferrocene is electron richer, which results in considerably different e-values (e-value (vinylferrocene) = -2.1; evalue (styrene) = -0.8 25) leading to non-ideal/non-azeotropic copolymerization parameters (r vinylferrocene = 0.08; r styrene = 2.63; (r vinylferrocene 6r styrene ) = 0.21; at 70 8C, initiated by AIBN in benzene 25,26) . In summary, the deviations from a controlled radical polymerization observed for the homo-and copolymerization of vinylferrocene in the presence of TEMPO are most likely due to the fact that the vinylferrocene monomer can act as a transfer agent.…”
Section: Results and Discussion (A) Random Copolymers P(s/vfc) And Pmentioning
confidence: 99%
“…This results in low molecular weights in a conventional radical polymerization initiated with AIBN (M -n above 12 000 g/mol is rarely described in literature). Also the double bond of vinylferrocene is electron richer, which results in considerably different e-values (e-value (vinylferrocene) = -2.1; evalue (styrene) = -0.8 25) leading to non-ideal/non-azeotropic copolymerization parameters (r vinylferrocene = 0.08; r styrene = 2.63; (r vinylferrocene 6r styrene ) = 0.21; at 70 8C, initiated by AIBN in benzene 25,26) . In summary, the deviations from a controlled radical polymerization observed for the homo-and copolymerization of vinylferrocene in the presence of TEMPO are most likely due to the fact that the vinylferrocene monomer can act as a transfer agent.…”
Section: Results and Discussion (A) Random Copolymers P(s/vfc) And Pmentioning
confidence: 99%
“…22,23 The number-average molecular weight of poly(VFE-co-MMA) and poly(VFE-co-St) was estimated to be 6:5 Â 10 4 and 4:2 Â 10 4 , respectively. The content of ferrocene moieties of poly(VFE-co-MMA) and poly-(VFE-co-St) were determined to be 14 mol % and 7 mol %, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The electroactive but pH insensitive vinylferrocene (VFc) has been polymerized by cationic [33], anionic [34], free radical polymerization [35], and more recently by 2,2,6,6-tetramethylpiperidinyl-1-oxy (TEMPO)-mediated free radical polymerization [36]. Numerous studies have been reported on the copolymerization of VFc, using 2,2'-azobisisobutyronitrile (AIBN) in organic solvent, with a variety of monomers, such as styrene, methyl methacrylate and isoprene [35].…”
Section: Introductionmentioning
confidence: 99%